Hunting for the progenitor of SN 1006: High resolution spectroscopic search with the FLAMES instrument - Kerzendorf, W; Schmidt, B; Laird, J; Podsiadlowski, P; Bessell, MS (2012)
Type Ia supernovae play a significant role in the evolution of the Universe and have a wide range of applications. It is widely believed that these events are the thermonuclear explosions of carbon-oxygen white dwarfs close to the Chandrasekhar mass (1.38 M\odot). However, CO white dwarfs are born with masses much below the Chandrasekhar limit and thus require mass accretion to become Type Ia supernovae. There are two main scenarios for accretion. First, the merger of two white dwarfs and, second, a stable mass accretion from a companion star. According to predictions, this companion star (also referred to as donor star) survives the explosion and thus should be visible in the center of Type Ia remnants. In this paper we scrutinize the central stars (79 in total) of the SN 1006 remnant to search for the surviving donor star as predicted by this scenario. We find no star consistent with the traditional accretion scenario in SN1006.